Realismus und Moderne in der Kleinen Prosa von Robert Musils "Nachlass zu Lebzeiten" - Goettsche, Dirk (De Gruyter, 2018)
This study proposes a new approach to Robert Musil’s engagement with the tradition of (German) Realism. It shifts the focus from his novellas and his novel "Der Mann ohne Eigenschaften" to the short prose of his "Nachlass zu Lebzeiten" (1936) while also developing a conceptual framework for the analysis of (legacies of) „Realism in Modernism“. In the first part of the essay a critical review of the 1970/80s debate about Musil’s realism paves the way for a reassessment of the relationship between Realism and Modernism in German literature in general and in Musil’s work in particular. The second part discusses Musil’s "Nachlass zu Lebzeiten" as an example of the function of elements of Realism in modernist short prose while also suggesting a rereading of the history of literary Realism from the perspective of the 19th century prose sketch and recent research in comparative literature.